Dogmatic Construction of Universal Legal Succession in the Field of Inheritance Law - O. Ye. Kukharyev (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the article is to clarify the essence of universal legal succession in the field of inheritance law.